1976
DOI: 10.1073/pnas.73.10.3433
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of hepatic glycogen synthesis by amino acids.

Abstract: Hepatocytes isolated from livers of fasted rats form little glycogen from glucose or lactate at concentrations below 20 mM. Glycogen is formed in substantial quantities at a glucose concentration of 60 mM. In the presence of 10 mM glucose, 20-30% as much glycogen as glucose-is formed from fructose, sorbitol, or dihydroxyacetone. The addition of either glutamine, alanine, or asparagine stimulates the formation of glycogen from lactate 10-to 40-fold. The formation of glucose and glycogen is then about equal, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

1977
1977
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(64 citation statements)
references
References 11 publications
3
61
0
Order By: Relevance
“…Hems et al [1] demonstrated that the presence of gluconeogenic precursors stimulate glycogen synthesis in the peffused liver of the starved rat. More recently, Katz et al [19] reported an effect of amino acids on glycogen synthesis in isolated hepatocytes. However, addition of insulin resulted in an increased glycogen synthesis in cultured parenchymal cells from both normal and diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Hems et al [1] demonstrated that the presence of gluconeogenic precursors stimulate glycogen synthesis in the peffused liver of the starved rat. More recently, Katz et al [19] reported an effect of amino acids on glycogen synthesis in isolated hepatocytes. However, addition of insulin resulted in an increased glycogen synthesis in cultured parenchymal cells from both normal and diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figures 3(a) and 3(c), glycogen formation was totally suppressed by 2-chloroadenosine, and this inhibition was accompanied by an increase in cyclic AMP. However, the inhibition of glycogen synthesis caused if the effects of ltu and amino acids It is well documented that amino acids stimulate glycogen synthesis from glucose and gluconeogenic precursors [7][8][9][10][11], and we determined whether Itu acts in a similar manner. Promotion of glycogen synthesis by added amino acids appears to be due to hepatocyte swelling after their uptake and the accumulation of intracellular catabolites such as glutamate and aspartate [34][35][36][37].…”
Section: Correlation Between Atp Content and Glycogen Formationmentioning
confidence: 99%
“…We had evidence that the known stimulating effect of amino acids on glycogen synthesis [7][8][9][10][11] may be due to a purine compound, since the increase in glycogen production by amino acids is strongly blocked by inhibitors of purine synthesis [8] and because this inhibition is correlated with a decrease of the formation of adenine nucleotides [12]. Adenosine has been reported to stimulate glycogen synthesis in vivo [13] and glycogen synthase activity in isolated liver preparations [1 1,14].…”
Section: Introductionmentioning
confidence: 99%
“…The low insulin/glucagon ratio used has previously been reported to stimulate net glucose output in perfused rat liver (33). Livers were perfused in a nonrecirculating set-up, and samples of 2 ml were drawn simultaneously from the inflow and outflow of the liver at t ϭ 0, 5,10,15,20,25,30,35, and 40 min. At t ϭ 40 min, 0.1 Ci/ml [U- 14 C]lactate (Amersham Biosciences) was added to the Krebs-Ringer buffer, and the perfusion was changed to a recirculating set-up (200 ml).…”
Section: Fig 1 Effect Of Dab On Glucose Release (A) Lactate Releasmentioning
confidence: 99%